Broadband bidirectional visible light absorber with wide angular tolerance. Issue 2 (15th December 2015) - Zhou, Lei; Zhou, Yun; Zhu, Yu-Fu; Dong, Xiao-Xuan; Gao, Ben-Ling; Wang, Yan-Zong; Shen, Su
Abstract : A wide-band bidirectional visible light absorber has been developed based on a quasi-periodic nanocone array coated with a dielectric-loaded Au monolayer. Abstract : High-performance light absorption devices have previously been obtained by coupling photons to conduction electrons. However, energy harvesting is limited in these devices because they only absorb light from one incident direction. We have developed a wide-band bidirectional visible light absorber (BLA) based on a quasi-periodic nanocone array coated with a dielectric-loaded Au monolayer. The proposed BLA is capable of simultaneously absorbing light from both the front and rear surfaces, yielding an average front absorption of 87.4% and a corresponding rear absorptivity of 76.2% in the range 300–700 nm. The bidirectional absorption properties were obtained at incident angles varying from 0 to 60°. Experimental and theoretical analyses indicate that these absorption properties can be ascribed to a combination of the localized cavity resonant mode, the localized surface plasmonic mode, the guided mode resonance, and hybrid coupling between the cavity resonant mode and the surface plasmonic mode. This concept provides a new pathway for the fabrication of new types of flexible or wearable solar thermoelectric devices, photodetectors, or other solid-state devices with large areas.